Clinical Features, Surgical Treatment, and Long-Term Outcome of a Multicenter Cohort of Pediatric Moyamoya - Zheng, Jun; Yu, Le-Bao; Dai, Ke-Fang; Zhang, Yan; Wang, Rong; Zhang, Dong (Frontiers in Neurology, 2019)
Objective: This study aims to investigate the clinical features, long-term outcomes, and prognostic predictors of a multicenter cohort of children with moyamoya disease. Methods: A series of 303 consecutive pediatric moyamoya disease (MMD) patients were screened in the present study. The clinical characteristics were retrospectively collected, and long-term outcomes was evaluated. Furthermore, logistic regression analyses were performed to determine the prognostic predictors for the clinical outcome. Results: The mean onset age at diagnosis was 9.4 years old. The gender ratio (girl-to-boy ratio) was 1.1:1.0. Among these 303 patients, 13 patients underwent different surgical modalities in bilateral hemispheres, while eight patients failed to follow-up, and were excluded. Therefore, a total of 282 patients were analyzed. Among these patients, 17 patients underwent combined bypass (CB), 47 patients underwent direct bypass (DB), 150 patients underwent indirect bypass (IB), and 68 patients underwent conservative treatment. Furthermore, recurrent stroke events were observed in 35 patients (12.4%). The Kaplan-Meier analysis demonstrated that there was no significant difference in either ischemia or hemorrhage-free time among the different surgical modalities (P = 0.67 and 0.79, respectively). Furthermore, longer ischemia-free time was observed in the surgical group, when compared to the conservative group (P < 0.01). In addition, 82.7% (177/214) of patients who underwent surgical treatment obtained good outcomes (mRS 0-1), which were significantly higher than the rate of patients who underwent conservative treatment (52.9%, 36/68; P < 0.01). The rate of patients with improved symptoms was also significantly different (93.0 vs. 16.2%, P < 0.01). However, no significant difference was observed in the rate of good outcomes, disability, and improved symptoms among the different surgical modalities. The logistic regression analyses revealed that postoperative ischemic events were the only risk factor associated with unfavorable clinical outcome (OR:3.463; 95% CI:1.436–8.351; P < 0.01). Conclusion: CB, DB, and IB might have similar effects on long-term clinical outcome in pediatric MMD. However, surgical revascularization is superior, when compared to conservative treatment. Furthermore, postoperative ischemic events were confirmed as potential prognostic factors associated with unfavorable clinical outcome.